2013
DOI: 10.1007/s11095-013-0996-5
|View full text |Cite
|
Sign up to set email alerts
|

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis

Abstract: The self-made DOC + MBs have potential as a new ultrasound contrast agent and drug-loaded microbubble, and can obviously enhance the antitumor effect of DOC under LFUS exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Moreover, the energy lose for low frequency ultrasound is low and hence deeper tissue can be treated. 8,9 In addition, our findings also demonstrated that these treatments would not damage the normal function of prostatic tissue, with no significant difference in renal function laboratory data (BUN, Cr, AST, and ALT).…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, the energy lose for low frequency ultrasound is low and hence deeper tissue can be treated. 8,9 In addition, our findings also demonstrated that these treatments would not damage the normal function of prostatic tissue, with no significant difference in renal function laboratory data (BUN, Cr, AST, and ALT).…”
Section: Discussionsupporting
confidence: 60%
“…Nano-scale MBs usually have the diameter within 1 lm. Under a certain acoustical condition, MBs physically interact with some target tissues and increase temporarily the drug uptake by cells with improved cell permeability [12][13][14]. Nevertheless, MB release of drugs and the drug uptake by cells hardly appear in tissues without ultrasound exposure.…”
Section: Introductionmentioning
confidence: 99%
“…J Drug Target, Early Online:[1][2][3][4][5][6][7][8][9][10][11][12][13] Journal of Drug Targeting Downloaded from informahealthcare.com by University of Otago on 07/28/15For personal use only.…”
mentioning
confidence: 99%
“…Secondly, low frequency ultrasound can induce cell membrane sonoporation and permeabilize the biological barrier, facilitating the transport of macromolecules and gene delivery [6,7]. Importantly, low frequency ultrasound has direct antitumor effect in vitro experiments, especially when combined with microbubbles [8,9]. Thus, low frequency ultrasound has prominent advantages in treatment of castration-resistant prostate cancer [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, low frequency ultrasound has direct antitumor effect in vitro experiments, especially when combined with microbubbles [8,9]. Thus, low frequency ultrasound has prominent advantages in treatment of castration-resistant prostate cancer [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%